Philanthropy among the Poor: Social Welfare Insights from the Family Hope Program Beneficiaries in Indonesia - Hatma Indra Jaya, Pajar; Saptoni, Saptoni (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2025)
To address social welfare issues, governments require public participation through philanthropic activities. As philanthropy is often viewed as the domain of the wealthy, many studies focus on elite philanthropy, with only few examining the contributions of the poor. Despite their circumstances, people in poverty have the potential to engage in philanthropic activities. Recent research indicates that individuals experiencing poverty can indeed become philanthropists. This study gathered information from beneficiaries of the Family Hope Program (Program Keluarga Harapan, PKH), a social assistance initiative for poor households in Yogyakarta, Indonesia. The findings reveal that philanthropic practices exist among the poor, albeit with distinct characteristics compared to those of the wealthy. Three key differences distinguish the philanthropy of the poor from that of the rich: form, motive, and effectiveness. Wealthy philanthropists typically donate substantial amounts of money or goods, whereas poor philanthropists offer a variety of contributions, including small amounts of money, goods, free assistance, lending household appliances, time, and even prayers. Many scholarly works show that wealthy individuals tend to engage in philanthropy during significant social welfare crises that attract public attention. In contrast, poor philanthropists are active whenever a community member faces social welfare issues. Instead of economic or political incentives, the motives for philanthropic activities among the poor stem from spiritual fervour and communal culture. Although the economic value of their contributions may be minimal, the philanthropy of low-income individuals effectively addresses welfare issues within their communities.